In vitro activation of procaspase-8 by forming the cytoplasmic component of the death-inducing signaling complex (cDISC) - Roy, Ankoor; Hong, Jong hui; Lee, Jin-Hee; Lee, Young-Tae; Lee, Bong-Jin; Kim, Key-Sun (KOREAN SOC MOLECULAR & CELLULAR BIOLOGY, 2008)
Procaspase-8 is activated by forming a death-inducing signaling complex (DISC) with the Fas-associated death domain (FADD) and the Fas receptor, but the mechanism of its activation is not well understood. Procaspase-8 devoid of the death effector domain at its N-terminus (Delta nprocaspase-8) was reported to be activated by kosmotropic salts, but it has not been induced to form a DISC in vitro because it cannot interact with FADD. Here, we report the production of full-length procaspase-8 and show that it is activated by adding the Fas death domain (Fas-DD) and the FADD forming the cytoplasmic part of the DISC (cDISC). Furthermore, mutations known to affect DISC formation in vivo were shown to have the same effect on procaspase-8 activation in vitro. An antibody that induces Fas-DD association enhanced procaspase-8 activation, suggesting that the Fas ligand is not required for low-level activation of procaspase-8, but that Fas receptor clustering is needed for high-level activation of procaspase-8 leading to cell death. In vitro activation of procaspase-8 by forming a cDISC will be invaluable for investigating activation of ligand-mediated apoptosis and the numerous interactions affecting procaspase-8 activation.